2017
DOI: 10.1002/jsfa.8606
|View full text |Cite
|
Sign up to set email alerts
|

How are arbuscular mycorrhizal associations related to maize growth performance during short‐term cover crop rotation?

Abstract: AMF variables and maize performance were related directly or indirectly to maize grain yield, whereas root colonization had a positive effect on maize performance. AMF may be an essential factor that determines the success of cover crop rotational systems. Encouraging AMF associations can potentially benefit cover cropping systems. Therefore, it is imperative to consider AMF associations and crop phenology when making management decisions. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 60 publications
6
29
1
Order By: Relevance
“…Overall, our study showed a stimulation of AMF in the subsequent crop when fallow was replaced by barley CC but not when fallow was replaced by vetch. Our results agreed with other field experiments in which the use of grass CCs, such as winter wheat ( Kabir and Koide , ; Higo et al, ), oat and rye ( Kabir and Koide , ; White and Weil , ), and ryegrass ( Higo et al, ), increased mycorrhizal colonization from 26% to two times in the subsequent maize crop. The lack of positive effect of vetch CC on the AMF parameters is contrary to our first hypothesis and disagrees with some studies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Overall, our study showed a stimulation of AMF in the subsequent crop when fallow was replaced by barley CC but not when fallow was replaced by vetch. Our results agreed with other field experiments in which the use of grass CCs, such as winter wheat ( Kabir and Koide , ; Higo et al, ), oat and rye ( Kabir and Koide , ; White and Weil , ), and ryegrass ( Higo et al, ), increased mycorrhizal colonization from 26% to two times in the subsequent maize crop. The lack of positive effect of vetch CC on the AMF parameters is contrary to our first hypothesis and disagrees with some studies.…”
Section: Discussionsupporting
confidence: 92%
“…Various studies have reported positive relationships between AMF presence after CC and plant nutrient content, especially when the P cycle is the focus (Njeru et al, 2014). Because of the AMF benefits to nutrition, some studies have indicated a relation between increased AMF colonization provided by CCs and the main crop yield (Karasawa and Takebe, 2012;Higo et al, 2018b), although this issue is controversial (Ryan and Kirkegaard, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This could be one reason why P fertilizer input did not change the diversity of the AMF communities in tomato plants. Additionally, the impact of soil P on the diversity of AMF communities still remains a controversial subject, and the results could be related to P application rates [80], sampling times [83], host plant species [84,85], and agricultural management [86][87][88][89][90]. Our results were inconsistent regarding P fertilization on the diversity of AMF communities compared to previous reports.…”
Section: Effect Of P Fertilizer Level On the Amf Communities In Tomatcontrasting
confidence: 80%
“…Community composition in every OTU grouping shifted between spring and summer sampling times, including groupings not affected by cover crop species identity (i.e., Insect Pathogens and Abundant OTUs). Strong effects of season and/or time on fungal communities, especially AM fungi, from cover crop treatments have been observed elsewhere [34][35][36][37] . The two main disturbances that occurred between the spring and summer sampling events were the addition of bedded dairy manure and tillage.…”
Section: Discussionmentioning
confidence: 74%
“…Genus-level abundances of OTUs assigned to the AM fungal group were dependent on cover crop identity, as well as CC Function. Previous studies have reported that cover crop effects on AM fungi, including biomass and community composition, seem to be dependent on cover crop species identity 19,21,23,25,[36][37][38][57][58][59] . Our study indicates that not only are the effects dependent on CC identity but they vary among genera of AM fungi.…”
Section: Discussionmentioning
confidence: 99%